2003
DOI: 10.1046/j.1365-2362.2003.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus induces apoptosis in uninfected bystander T cells and leads to granzyme B and caspase activation in peripheral blood mononuclear cell cultures

Abstract: Measles virus-infected monocytes induce apoptosis in uninfected T cells, suggesting that infected monocytes probably interact via cell-surface molecules with uninfected T cells and induce apoptosis by indirect mechanisms. Apoptosis of the lymphocytes may contribute to the pathogenesis of MV-induced immunosuppression and cell loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Fas loss of function or expression has been reported to accompany malignant phenotypes (55). Measles virus infection has previously been shown to result in Fas up-regulation in peripheral blood mononuclear cells (25) and dendritic cells (24), both in cell culture and in measles patients (26). Fas upregulation is also a significant determinant of lymphopenia observed in the context of natural measles virus infection (26).…”
Section: Discussionmentioning
confidence: 99%
“…Fas loss of function or expression has been reported to accompany malignant phenotypes (55). Measles virus infection has previously been shown to result in Fas up-regulation in peripheral blood mononuclear cells (25) and dendritic cells (24), both in cell culture and in measles patients (26). Fas upregulation is also a significant determinant of lymphopenia observed in the context of natural measles virus infection (26).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there has been no report that Vero cells express FasL, so it seems unlikely that apoptosis in CDV-infected Vero cells was triggered by the FasL-bound Fas receptor. In the case of measles virus (MV), which belongs to the genus Morbillivirus, MV-infected peripheral blood mononuclear cells (Vuorinen et al, 2003) and dendritic cells (Servet-Delprat et al, 2000a) have been shown to induce apoptosis in uninfected T cells via the Fas/FasL pathway (Servet-Delprat et al, 2000b). With respect to the Sendai virus (Sv), which, like CDV, belongs to the subfamily Paramyxovirinae, it has been reported that induction of host cell apoptosis by Sv in vitro requires the activation of caspase-8 but does not require FasL (Bitzer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of morbilliviruses, infection-induced apoptosis of immune cells has been proposed as a main factor contributing to the observed leukopenia and the resulting immune suppression (10). There is experimental evidence for apoptosis induction, either directly in infected cells or as a bystander effect in noninfected cells (18,25,41), as well as for inhibition of apoptosis in the context of viral interference with the host response on a cellular level (7,37). To gain better insight in the extent of apoptosis in immune tissues during the crucial early stages of a natural infection, we assessed levels of early and late apoptosis at different time points during the first week after infection in ferrets infected with a wild-type CDV strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bystander apoptosis of noninfected CD3 ϩ cells has been observed after in vitro infection of human peripheral blood mononuclear cells (PBMCs) (12,41). These observations have been supported by direct analyses of PBMCs from MeV patients, where high levels of proapoptotic noninfected cells were found (25,26).…”
mentioning
confidence: 84%